A MÍDIA INCITANDO ESTILOS DE VIDA SAUDÁVEIS: UMA ANÁLISE DO QUADRO "MEDIDA CERTA" DO PROGRAMA FANTÁSTICO - Sandro Faccin Bortolazzo; Roseli Belmonte Machado (Universidade Estadual do Oeste do Paraná, 2014)
This article aims to analyze how certain practices disseminated by media apparatuses have been acted in the knowledge production about the body and health. On the analysis, we used as empirical material a television series - conveyed by the program called Fantastic from Rede Globo and titled as "Medida Certa". Thus, we suggest discussing how the triggering of certain features such as the specialists speeches in health field, the use of known personalities, among others, end up producing "truths" about our society and guiding the adoption of healthy lifestyles. These speeches while stimulating the subjects to become active and healthy also make them responsible for their own health care. From the TV program analysis, it was possible to perceive how certain knowledge about the investments in itself and the responsibility from individuals to take care of your body has operated as pedagogical practice to the extent that teach us ways of being healthy. In addition, the study highlights the health issue as a market product, ie at the intersection of several strategies, the TV program leads subjects to act as managers for healthy lifestyle.